The First Draft Merchant Shipping, Bill: Should South Africa implement the proposed amendments in section 271 of the Bill, in its current form? - Msiza, Sharon Phumzile (Department of Commercial Law, 2020)
For over a period of over sixty years, South Africa has applied the provisions of the MSA enacted in 1951 to matters relating to shipowner’s right to limit liability. Since then, Parliament has made several attempts at amending the MSA with no success. However, determining whether South Africa should implement the proposed amendments in terms of the MSA Draft Bill, is an inquiry that should not only include a comparison of the old order with the newly proposed order, but, it should also require reasons as to why the reform should be achieved in a particular manner. This is important because knowing what the discrepancies of the current dispensation are, will enable us to evaluate whether the newly proposed amendments will address them.